(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The relationship between tobacco and alcohol use is very important in making strategies containing use of these products. Alcohol and tobacco use were studied separately in Indian studies, which can undermine their co-occurrences. The objective of the study is to know the prevalence and socio-economic determinants of co-occurrence of alcohol and tobacco use among men in working age groups. Data Sources: The data from the Study on Global Ageing and Adult Health (SAGE) Wave1 was used. It was a cross sectional household survey, which collected information for adults aged 18 years and above. Results: The prevalence of co-use of tobacco and alcohol among men aged 18-59 years was 23.5%. High use of tobacco was found among alcohol user. Age cohorts were also the important determinants of alcohol and tobacco use. The inverted U or V-shape relation was found between age groups and co-use of tobacco and alcohol. The prevalence was lowest for age groups 18-24 years and 50-59 years. Low education attainment and working in informal sector were the main risk factors for high co-use of these substances among men. The study also tried to look at the relationship between the co-use of alcohol and tobacco with some selected health indicators. Use of alcohol and tobacco was significantly related with under nutrition and increasing blood pressure levels among men in India. Conclusion: To contain the use of alcohol and tobacco to improve heath condition among adult men, policies and strategies must be form keeping the importance of their co-occurrences.